Periphytic Cosmarium (Zygnematophyceae, Desmidiaceae) in lentic environments of the Upper Paraná River floodplain: Taxonomy and ecological aspects - Osório,Nicolli Cristina (2018)
Abstract Aim A taxonomic study of the species of the genus Cosmarium Corda ex Ralfs (Desmidiaceae) was conducted in two lentic environments of the Upper Paraná River Floodplain (Garças and Patos lakes). Methods The samples were collected in November 2016. Two petioles of Eichhornia azurea (Sw) Kunth were sampled and analyzed qualitatively. Results Six species, nine varieties, and three forms were identified, with five taxa being common to both lakes, nine in Garças Lake, and four in Patos Lake. Of this, thirteen species represent the first records for the floodplain environment. Conclusion This study contributes to the knowledge of the biodiversity of this region, providing support for future ecological studies and biomonitoring.